The Effect of Soybean Ethanol Extract in Tnf-? Levels of Huvecs Culture Induced by Preeclampsia Plasma - Mestika, Luh Citrarasmi Dara; Aslina, Wiwit Indriyani; Dyantari, Putu Eva Yuni; Laksmi, Ni Putu Citra; Sumiati, Sumiati (Riviera Publishing, 2026)
The main characteristics of preeclampsia are endothelial dysfunction and inflammatory response of the immune system. Oxidative stress contributes to the pathogenesis of preeclampsia by increasing tumor necrosis factor-? (TNF-?) due to increased reactive oxygen species (ROS). Isoflavones are known to be able to prevent endothelial dysfunction due to increased ROS and proinflammatory cytokines. This study aims to determine the effect of soybean extract on TNF-? associated with preeclampsia using the endothelial cell culture method. The study using in vitro design with human umbilical vein endothelial cells (HUVECs) cultures sample induced by normotensive plasma and preeclampsia plasma and then given various doses of soybean ethanol extract. The TNF-? level of each observation group was determined by the enzyme-linked immunosorbent assay (ELISA) procedure. Statistical analysis were performed with One-Way ANOVA test using SPSS Version 25. Statistical analysis showed a significant difference (p < 0.05) in TNF-? levels of HUVECs cultures exposed to preeclampsia plasma. Compared to the group exposed only to preeclampsia plasma (223.975±5.222ng/mL), the model given a dose of 35 ppm soybean ethanol extract showed a significant decrease in TNF-? levels (178.350±10.093ng/mL), similar to the control group exposed to normal plasma (185.993±16.393ng/mL). This study results indicate that the bioactive compounds in soybean ethanol extract assumed can reduce TNF-? levels in HUVECs cultures induced by preeclampsia plasma and have a potential future therapy for preeclampsia.